TEACHERS’ EXPERIENCE IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNER AT ELEMENTARY SCHOOL BANDUNG - Lukman, Nazhifah Madina; Hidayat, Hamdan; Gaffar, Andriana (TELL - US JOURNAL, 2025)
This study aims to explore the experiences and strategies employed by English teachers in teaching vocabulary to young learners at an elementary school in Bandung. The research focuses on how teachers implement vocabulary teaching techniques, the types of media and materials they use, and the challenges they face during instruction. Employing a qualitative descriptive approach, data were collected through semi-structured interviews, and document analysis involving two English teachers at a private elementary school The findings reveal that both teachers apply a combination of interactive and varied techniques including games, storytelling, flashcards (physical and digital), and smartboard usage to engage students actively in vocabulary acquisition. The multisensory approach and incorporation of diverse media proved effective in increasing student motivation, participation, and retention of vocabulary. However, challenges such as classroom management and sustaining student attention were evident, highlighting the need for continuous professional development and supportive institutional frameworks. This study underscores that comprehensive vocabulary instruction combining multiple strategies and media can enhance young learners’ English vocabulary mastery and suggests schools invest in teacher training and adequate teaching resources to improve the quality of elementary English education